Analisis Implementasi Prinsip Ekonomi Islam dalam Sistem Keuangan Modern di Indonesia - Ahmad Sulton Ariwibowo; Mohammad Muksi; Ahmad Subakir; Mohammad Qomarul Huda; Rega Nosa Yonanda (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
The expansion of Indonesia’s financial sector has been accompanied by the development of Islamic financial institutions as an alternative to conventional finance. Despite their growth, the integration of Islamic economic principles into the modern financial system remains subject to various structural and operational challenges. This study aims to examine the implementation of Islamic economic principles within Indonesia’s financial system, identify factors influencing their application, and assess their contribution to the development of the Islamic finance industry. Employing a qualitative approach with a descriptive-analytical method, this research is based on library studies using primary sources from the Qur’an and Hadith, complemented by secondary data from academic literature, scholarly journals, and official reports. The findings indicate that Islamic economic principles have been institutionalized through Islamic banking, takaful (Islamic insurance), and Islamic capital market instruments. Their implementation has been supported by regulatory development, institutional expansion, and increasing public awareness of Islamic finance. However, several constraints persist, including relatively low levels of Islamic financial literacy, limitations in human resource capacity, and the need for greater product diversification and innovation. The study further finds that the contribution of Islamic finance to the broader financial system remains below its potential, reflecting gaps between regulatory objectives, market penetration, and institutional performance. These findings suggest that strengthening literacy, human capital development, and innovation strategies are important factors in enhancing the role of Islamic economic principles within Indonesia’s contemporary financial system.